_marry bone_ (1971)
marry bone In my home a belief quite common today, is connected with two knives. First of all, if you are at the table and two knives are crossed at your place this is a sign of bad luck. If, however the two knives are at your place but not crossed then it is believed that you will have two wives. Another belief centers around what we called the "_marry bone_" found in chicken and other birds. This bone is taken and roasted , then two people break the bone by holding on to the tip of each end. Whoever gets the longest end is going to be married . ->something like the bone is. See cited quotation. Yes Love/marriage DICT CEN JW Not used Not used Withdrawn [see 'marry-tot', 'rocky bone'] 'wish bone' etc Drawing of "marry bone" included.